Loss of genetic diversity among pirarucu broodstocks in fish farms: a pilot study - Santos, Jeremias Silva dos; Guerreiro, Sávio; Medeiros, Natalia Bianca Caires; Alves, Kaliandra; Hamoy, Igor; Nunes-Rodrigues, Marilia (Scientia Agraria Paranaensis, 2022)
Molecular markers can be used to monitor genetic variability in cultivated fish stocks with the aim of developing better aquaculture techniques and increasing productivity. In view of the above, the objective of the present work was to evaluate the genetic variability in pirarucu broodstocks in fish farms in the southeast and northeast of the of Pará state, Brazil. The samples were genotyped using four microsatellite markers, and genetic diversity indices were calculated for each broodstock. A total of 16 alleles were identified from the four loci tested in the 33 pirarucu samples, with means of 3.00, 2.75, and 2.25 alleles per locus in broodstocks from Tucumã, Parauapebas, and Moju municipalities, respectively. The Parauapebas broodstock had the highest mean observed heterozygosity. In the broodstocks from Tucumã and Parauapebas, the markers AgCAm16 and AgCAm18 were not at Hardy-Weinberg equilibrium. This pilot study showed that there were considerable losses of genetic variability in pirarucu breeding centers in the municipalities of Tucumã, Parauapebas and Moju compared to the variability in the natural populations of this fish species.